2022
DOI: 10.3389/fimmu.2022.913483
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Neoadjuvant Monoimmunotherapy With PD-1 Inhibitor for dMMR/MSI⁃H Locally Advanced Colorectal Cancer: A Single-Center Real-World Study

Abstract: ObjectiveTo explore the efficacy and safety of single-agent programmed cell death protein-1 (PD-1) inhibitor in the neoadjuvant treatment of patients with mismatch repair-deficient (dMMR) or microsatellite instability-high (MSI-H) locally advanced colorectal cancer (LACRC) through single-center large⁃sample analysis based on real⁃world data in China.MethodsThis study was a retrospective, single-center, case series study. 33 colorectal cancer (CRC) patients with clinical stage of T3~4N0~2M0 treated in Yunnan Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…[20] Immunotherapy has also shown some preliminary results in neoadjuvant treatment for locally advanced rectal cancer. [31][32][33][34] As research progresses, individualized treatment plans need to be developed for specific patients.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Immunotherapy has also shown some preliminary results in neoadjuvant treatment for locally advanced rectal cancer. [31][32][33][34] As research progresses, individualized treatment plans need to be developed for specific patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested favorable pathological outcomes following neoadjuvant chemoradiotherapy plus targeted therapy ( 31 , 32 ). Immunotherapies, such as programmed cell death-1 or programmed cell death-ligand 1 inhibitors, also demonstrate encouraging clinical benefits including response rate, and the immune checkpoint represent a useful target to enhance tumor regression ( 33 , 34 ). Further investigation in a large cohort study is needed to improve prognosis in patients who are resistant to TNT.…”
Section: Discussionmentioning
confidence: 99%
“…From these, 8 studies met the eligibility criteria. [11][12][13][14][15][16][17][18] No new studies were included in the PubMed search between April and September 2023. A flow diagram is in Supplemental Figure 1 at http://links.…”
Section: Systematic Reviewmentioning
confidence: 99%